Entrepreneurship Education and Training as Facilitators of Regional Development: A Systematic Literature Review - Galvão, Anderson Rei (2019)
Purpose - The purpose of this paper is to provide insights of a systematic literature review (SLR) of the entrepreneurship education and training as facilitators of regional development. Current and future trends in the field are identified. Design/methodology/approach – The paper offers an SLR on the entrepreneurship education and training and advances through a comprehensive bibliometric analysis comprising the period 1973-2016. To collect data, only articles published in scientific journals were used in the SCOPUS database. Findings – The results highlight that both training and entrepreneurship education can be a strong strategic tool for regional development, and that it is important for entities such as academia, government and business to cooperate towards the same goal in order to strengthen the entrepreneurial intention of society. Findings reveal three clusters as trends of literature: entrepreneurial universities, entrepreneurial spirit and process of business creation. Originality/value – This paper contributes to fill the gap in terms of SLR on the importance of entrepreneurship education and training for regional development conducted by a bibliometric analysis. Keywords Entrepreneurship, Regional development, Bibliometric analysis, Systematic literature review, Education and training, Entrepreneurial universities